A dynamic voting scheme in distributed systems - Davcev, D. (IEEE transactions on software engineering, 1989)
A dynamic weighted voting scheme for consistency and recovery control of replicated files in distributed systems is presented. The purpose of a replicated file is to improve the availability of a logical file in the presence of site failures and network partitions. The accessible physical copies of a replicated file will be mutually consistent and behave as a single copy. The recovery scheme requires no manual intervention. The control scheme tolerates any number of site failures and network partitions as well as repairs. Correctness results are given.< >